Job Satisfaction Among Public Sector Doctors and Nurses in India. (December 2021) - Purohit, Bhaskar; Lal, Sham; Banopadhyay, Tathagata
In most countries, the efforts to attract and retain health workers have been focused on extrinsic measures of motivation, with very less focus on a better understanding of job satisfaction—an important intrinsic factor and construct. The main aim of this study was to assess job satisfaction, its seven dimensions, and motivation among health service providers (doctors and nurses) employed within the public sector in India. The study was conducted in three districts representing two states in India. The study participants represent the doctors and nurses from public health and service delivery centres. Data were collected from a total of 307 healthcare providers (152 doctors and 157 nurses). 'Measure job satisfaction' tool was adapted that contained 41 items capturing seven dimensions of job satisfaction on a five-point Likert scale with a higher score indicating a higher level of job satisfaction and vice versa. In addition, one single statement was used to assess motivation. Average scores were calculated for each of the seven dimensions of job satisfaction, motivation and for overall job satisfaction. Parametric tests such as t -test and analysis of variance (ANOVA) were used for comparisons of job satisfaction scores according to the place of work, years of work experience, appointment type and health professional categories. The statistical analysis was carried out using SPSS version 22.0. Exploratory factor analysis was carried out to assess the relationship between job satisfaction and motivation and regression analysis of motivation was carried to assess predictors of job satisfaction, demographic and work-related factors' effect on motivation. The average scores for most of the dimensions of job satisfaction were low for both doctors and nurses with the lowest scores reported for the dimensions of 'professional support' and 'personal satisfaction' while the highest score reported for 'satisfaction with pay'. Significant results in the difference of mean scores were found for all seven dimensions of job satisfaction except for 'prospects' at different levels of place of work, 'standard of care' at different levels of length of service and 'training' for different levels of types of appointment. The mean scores of motivation were found to be significantly different for different levels of place of work and also between the doctors and nurses. The regression analysis of motivation on various predictors of job satisfaction suggests that personal satisfaction and satisfaction in prospect were highly significant while other variables such as gender and place of posting were marginally significant. Understanding of job satisfaction can provide useful insights to both extrinsic as well as intrinsic aspects of work motivation, which arguably is the most critical area of health systems research that could potentially feed into streamlined and improved health workforce management policies aimed at addressing the shortage and retention of the health workforce.